Native fungal microorganisms enhance important agronomic traits in barley by - Hodkinson, Trevor R.; Murphy, Brian R. (Graduate Students’ Union of the University of Dublin, Trinity College, 2015)
Successfully addressing the challenge of providing future food security will require both improvements in crop yield as well as the cultivation of additional farmland. This may result in the steady increase of farming on marginal, arid, and semiarid lands, especially in the developing world, leading in turn to greater biotic and abiotic stresses on crops. To enable crops to deal with these stresses, an evergrowing arsenal of chemicals will be needed to maintain acceptable yields, with consequent environmental damage and maybe even the loss of biodiversity. Any means of reducing these chemical crop inputs would be welcome, and a class of microorganisms called endophytes may provide part of the solution. We have isolated fungal endophyte strains from wild populations of Irish plants and carried out a number of experiments which assessed the effect of inoculating these endophytes onto barley (Hordeum vulgare L.) in a variety of stressful growing conditions. We have found that the endophytes induced improvements in important agronomic traits in nearly every situation, including 29% and 70% increases in grain yield and shoot biomass respectively in nutrient-stressed barley; 100% suppression of seed-borne barley diseases; 50% increase in both the number of shoots and grain yield in droughtstressed barley; and finally, a 600% increase in plant survival in multiply-stressed barley. These results suggest that the endophyte strains that we have isolated could provide the basis for the development of a commercially-viable biotechnological means of reducing chemical crop inputs, and we are currently working on such a project with industry partners.
Keywords: Biofertilisation; Biocontrol; Agriculture; Endophytes; Barley